Ubiquitin‐specific protease‐like 1 (USPL1) is a SUMO isopeptidase with essential, non‐catalytic functions - Schulz, Sarah; Chachami, Georgia; Winter, Ulrike; Stankovic-Valentin, Nicolas; Haas, Petra; Wittbrodt, Joachim; Meulmeester, Erik; Melchior, Frauke (EMBO reports, 2012)
Isopeptidases are essential regulators of protein ubiquitination and sumoylation. However, only two families of SUMO isopeptidases are at present known. Here, we report an activity‐based search with the suicide inhibitor haemagglutinin (HA)‐SUMO‐vinylmethylester that led to the identification of a surprising new SUMO protease, ubiquitin‐specific protease‐like 1 (USPL1). Indeed, USPL1 neither binds nor cleaves ubiquitin, but is a potent SUMO isopeptidase both in vitro and in cells. C13orf22l—an essential but distant zebrafish homologue of USPL1—also acts on SUMO, indicating functional conservation. We have identified invariant USPL1 residues required for SUMO binding and cleavage. USPL1 is a low‐abundance protein that colocalizes with coilin in Cajal bodies. Its depletion does not affect global sumoylation, but causes striking coilin mislocalization and impairs cell proliferation, functions that are not dependent on USPL1 catalytic activity. Thus, USPL1 represents a third type of SUMO protease, with essential functions in Cajal body biology.
Gesehen am 13.02.2017